Efektifitas Penggunaan Media Cat Air dalam Mengenalkan Warna Kombinasi pada Anak Usia Dini di TK Manbaul Ulum - Toyyib, Moh (STIT Al - Ibrohimy Bangkalan, 2024)
This article proves that the use of watercolor media can provide convenience for young children (AUD) in understanding and creating new colors through the process of mixing basic colors. This research was conducted at Mambaul Ulum Kindergarten, West Lantek Village. The introduction of color combinations is a very urgent part of developing creativity in early childhood (AUD). Watercolor media is an effective tool to support this learning process because it is flexible, interesting and easy for children to use. This research aims to identify the effectiveness of using watercolor media in introducing the concept of color combinations to young children. The method used is a descriptive qualitative approach through observation and documentation of children's activities when using watercolors. The results of the research show that through watercolor media, children can more easily understand and create new colors through the process of mixing basic colors. This activity also encourages the development of children's fine motor skills, imagination and creative thinking skills. But some children have difficulty controlling brush movements and mixing colors well. This may be due to lack of experience and fine motor skills that are not yet fully developed at their age. To overcome this, researchers provided more intensive guidance and support to these children. Apart from that, the children looked enthusiastic and more involved in learning activities.